Morphology of the enamel-cementum microvascular junction of the mouse incisor - Wong Ronnie S.F; Sims Milton R. (Sciendo, 1983)
Scanning electron microscopy of methyl methacrylate vascular perfusion casts with stereopair imaging has been used to provide three-dimensional morpholgy of the mouse incisor periodontal ligament microvascular bed. Both the cementum and enamel related incisor vascular beds have a distinct vascular architecture demarcated by a "boundry zone" of anastomsing vessels extending along the length of the tooth. The microvascular bed overlying the enamel is separated from the alveolar wall by a dense venour system. This investigation provides the first description of the rodent incisor "boundry zone" and the related vasculature using plastic injection replicas.